Frequency of toxigenic Fusarium species and fusariotoxins in wheat grain in Serbia - Stanković Slavica Ž.; Lević Jelena T.; Krnjaja Vesna S.; Bočarov-Stančić Aleksandra S.; Tančić Sonja L.; Kovačević Tamara M. (Zbornik Matice Srpske za Prirodne Nauke, 2007)
A total of 88 and 40 wheat samples collected immediately prior to harvest in 2005 and 2006, respectively, under different agroecological conditions, were studied in respect to the occurrence of Fusarium spp. and the production of fusariotoxins. The greatest number of samples was infected with species of the genera Fusarium (81.8 and 65.0%), and Alternaria (36.3 and 17.5%) with the intensity ranging from 9.4 to 84.0% in 2005 and from 23.4 to 80.6% in 2006. Out of 13 identified species belonging to the genus Fusarium, F. graminearum had the highest frequency (35.2 and 12.5%) and the intensity up to 67.2%, and 21.9%, in 2005 and 2006, respectively, followed by F. poae but only in 2005 (20.4%), and F. proliferatum in 2006 (19.7%). The natural occurrence of mycotoxins in positive samples varied from 37 to 331 ppb for zearalenone and from 31 to 125 ppb for diacetoxyscirpenol (DAS) and T-2 toxin. The concentration of mycotoxins amounted, on average, to 133.4, 61.0 and 45.7 ppb for zearelenone, DAS and T-2 toxin, respectively.